2009
DOI: 10.1111/j.1600-0633.2008.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Diel and seasonal changes in nutritional condition of the anadromous twaite shad Alosa fallax fallax (Lacépède, 1803) larvae

Abstract: Diel and seasonal changes in nutritional condition of the anadromous twaite shad Alosa fallax fallax (Lacépède, 1803) larvae Esteves E, Pina T, Andrade JP. Diel and seasonal changes in nutritional condition of the anadromous twaite shad Alosa fallax fallax (Lacépède, 1803) larvae.Abstract -In this work we aim to study: (i) the diel and seasonal changes in nutritional condition, herein RNA ⁄ DNA ratios, of twaite shad (Alosa fallax fallax) larvae and (ii) the influence of environmental and biological covariates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
2
2
0
Order By: Relevance
“…Diel patterns in our study were only recorded when data between species was pooled perhaps due a too small sample size given the intraspecific variation. In general, there is a clear response of RNA/DNA ratio to diel physiological fluctuations [30] as described for other species such as molluscs [23] and fish [22]. In our study, both species showed a winter pattern of lowest RNA/DNA ratio at noon and highest at midnight, while summer patterns were more variable, with highest RNA/DNA ratio in the day time, possibly since physico-chemical factors showed stronger diel fluctuations in summer then winter.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Diel patterns in our study were only recorded when data between species was pooled perhaps due a too small sample size given the intraspecific variation. In general, there is a clear response of RNA/DNA ratio to diel physiological fluctuations [30] as described for other species such as molluscs [23] and fish [22]. In our study, both species showed a winter pattern of lowest RNA/DNA ratio at noon and highest at midnight, while summer patterns were more variable, with highest RNA/DNA ratio in the day time, possibly since physico-chemical factors showed stronger diel fluctuations in summer then winter.…”
Section: Discussionsupporting
confidence: 73%
“…Previous work suggests that diel cycles are set by the availability of demersal planktonic food [17], [18] and alternate sources of nitrogen [19] with high concentration of zooplankton and possible highest feeding rates during night [20], [21]. Diel variations in RNA/DNA ratios have been observed for fish and molluscs [22], [23] due to diel fluctuations in metabolic rates, food requirements and digestion times [24]. However, to our knowledge no study so far has investigated diel patterns in RNA/DNA ratio and protein concentration, or investigated which physico-chemical factors might be responsible for these changes.…”
Section: Introductionmentioning
confidence: 99%
“…The recent human derived changes have altered water thermal and haline regimens and consequently the estuary production and food availability patterns as a result of river flow regulation (Morais et al, 2009). These changes in water parameters could have significant effects on anadromous species effective recruitment as suggested by Esteves et al (2009) and supported by current results. To improve the condition of nursery habitats, ecological flows should be implemented in order to achieve a balance between leading environmental factors, such as temperature and salinity, and enhance A. fallax recruitment (Chícharo et al, 2006).…”
Section: Discussionsupporting
confidence: 53%
“…As the spawning season progresses (from March to June) later larvae cohorts may benefit from increasing water temperature. From RNA/DNA ratios, Esteves et al (2009) found that metabolic activity is potentiated by the higher temperatures to which A. fallax larvae are exposed later in the spawning season, which also potentiate general ecosystem productivity providing larvae with a higher abundance of resources (Crecco and Savoy, 1985). In contrast, Esteves and Andrade (2012) observed that the highest growth rates for A. fallax larvae occurred early in the spawning season, suggesting that maybe only the fastest growing larvae survive during this period.…”
Section: Discussionmentioning
confidence: 99%